Pharyngeal fibromatosis presenting as adenoid hypertrophy: A case report and review of literature - Segun Segun-Busari; Adekunle David Dunmade; Biodun Sulyman Alabi; Kayode Adebamiji Adeniji; Olushola Abdulrahman Afolabi; Habeeb Kayodele Omokanye; Isaac Olarewaju Ajayi (Sahel Medical Journal, 2013)
A 10-year-old girl presented with a noisy breathing noticed from birth and failure to thrive. Examination revealed a huge lobulated firm mass in the oropharynx (toward the left side). Plain radiography of the neck showed a huge circumscribed pharyngeal mass extending from the base of the tongue to the level of the fourth cervical vertebrae. The mass measuring 6 cm Χ 5 cm was excised through a left lateral pharyngotomy. Histological examination showed sections of highly cellular interlacing bundles of fibroblast with moderate hyalinization extending to the surrounding fibro-fatty tissue. The cells have spindle nuclei with tapering ends. Occasional mitosis and in some areas myxoid degeneration were seen. A diagnosis of pharyngeal fibroma was made. Patient had an uneventful post-operative recovery with complete resolution of symptoms for the past 6 years. This rare benign tumor has not previously been reported at this site and may thus give rise to difficulty in diagnosis or to a misdiagnosis.